A novel polymorphic repeat in the upstream regulatory region of the estrogen-induced gene EIG121 is not associated with the risk of developing breast or endometrial cancer. (December 2016) - Bolton, Katherine; Holliday, Elizabeth; Attia, John; Bowden, Nikola; Avery-Kiejda, Kelly; Scott, Rodney
Abstract Background The estrogen-induced gene 121 (EIG121 ) has been associated with breast and endometrial cancers, but its mechanism of action remains unknown. In a genome-wide search for tandem repeats, we found thatEIG121 contains a short tandem repeat (STR) in its upstream regulatory region which has the potential to alter gene expression. The presence of this STR has not previously been analysed in relation to breast or endometrial cancer risk. Results In this study, the lengths of this STR were determined by PCR, fragment analysis and sequencing using DNA from 223 breast cancer patients, 204 endometrial cancer patients and 220 healthy controls to determine if they were associated with the risk of developing breast or endometrial cancer. We found this repeat to be highly variable with the number of copies of the AG motif ranging from 27 to 72 and having a bimodal distribution. No statistically significant association was identified between the length of this STR and the risk of developing breast or endometrial cancer or age at diagnosis. Conclusions The STR in the upstream regulatory region ofEIG121 is highly polymorphic, but is not associated with the risk of developing breast or endometrial cancer in the cohorts analysed here. While this polymorphic STR in the regulatory region ofEIG121 appears to have no impact on the risk of developing breast or endometrial cancer, its association with disease recurrence or overall survival remains to be determined.